2020
DOI: 10.1186/s12882-020-01915-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features and outcomes between patients with early and delayed lupus nephritis

Abstract: Background Lupus nephritis is associated with increased risk of end-stage renal disease (ESRD) and all-cause mortality. We evaluated the clinical features and outcomes of patients with early and delayed lupus nephritis. Methods The medical records of 171 patients who met the 1997 revised classification criteria for systemic lupus erythematosus (SLE) with pathologic confirmation of lupus nephritis were reviewed. Early lupus nephritis was defined when lupus nephritis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Almost all the previous reports confirmed the high frequency of III, IV and V classes of LN in lateonset LN. [8][9][10][11]15 Our analysis of the clinical and laboratorial features of our 226 LN biopsy proven patients demonstrated that whether the nephritis onset is very early, early, medium, late and very late onset, these groups broadly share same clinical and serological characteristics although as above, Caucasian origin; arthritis and leucopaenia, seem to be more common in those patients whose renal disease becomes evident > 10 years after diagnosis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Almost all the previous reports confirmed the high frequency of III, IV and V classes of LN in lateonset LN. [8][9][10][11]15 Our analysis of the clinical and laboratorial features of our 226 LN biopsy proven patients demonstrated that whether the nephritis onset is very early, early, medium, late and very late onset, these groups broadly share same clinical and serological characteristics although as above, Caucasian origin; arthritis and leucopaenia, seem to be more common in those patients whose renal disease becomes evident > 10 years after diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…Perhaps not surprisingly there are a number of differences amongst the previously reported series and in our experience. Tian et al 8 found no difference in terms of "kidney outcome comparing their early onset [less than 5 years] and late onset [more than 5 years] cases and these findings were reproduced by Ugoleni Lopez et al 9 and Ahn et al 10 . These data are broadly in line with our own results although the trend to end-stage renal disease in those whose nephritis diagnosis began more than 15 years after diagnosis was high [5 out of 10, 50%] compared to those whose nephritis began earlier [28 out of 216, 13%].…”
Section: Discussionmentioning
confidence: 75%
“…Moon, et al [35] reported that patients with delayedonset LN (de ined as newly developed LN after the onset of SLE) progressed more to CKD, than patients with initialonset LN (de ined as LN diagnosed at the time of SLE onset) (28% vs. 16%; p = 0,004), while Ahn, et al [52]. reported no difference in renal and overall survival rates between delayed-onset and initial-onset.…”
Section: Discussionmentioning
confidence: 99%
“…12 Ahn et al stated that CRP levels may be a predictive marker for end-stage renal disease. 38 Furthermore, it seems that indices such as neutrophil-to-lymphocyte ratio (NLR, demonstrating increased values in LN) and platelet-to-lymphocyte ratio can demonstrate a positive correlation with CRP. 39 However, whether or not these relationships are maintained in the presence of anti-CRP antibodies (or influenced by the latter) could be a subject of future research.…”
Section: Anti-crp Antibodies In Lupus Nephritismentioning
confidence: 99%